2000
DOI: 10.1002/1099-0690(200007)2000:14<2513::aid-ejoc2513>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Evaluation of (+)-Lactacystin and Analogs

Abstract: Since its isolation in 1991, (+)-lactacystin (1) has attracted considerable attention among leading synthesis laboratories due to its highly selective and potent inhibition of the 20S proteasome. The syntheses of this molecule described herein demonstrate several important strategies in the area of acyclic stereocontrol including the use of chiral metal enolate and chiral allylmetal-based bond construction methods. Figure 1) is a secondary metabolite derived from a streptomyces bacterial strain (OM-6519) [a] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 48 publications
1
39
0
Order By: Relevance
“…22 Hydroxyleucine derivatives such as 127 have been used as key synthetic intermediates in a number of syntheses of (ϩ)-lactacystin (128) with the result that a number of synthetic strategies have been developed to provide access to this building block. 22, 88 The AA based strategy remains among the shortest and most efficient approaches to this structural unit. 88,89 A related approach has been reported for the enantioselective synthesis of the hexahydroazepine core of (Ϫ)-balanol (129).…”
Section: Reverse Regioselectivitymentioning
confidence: 99%
“…22 Hydroxyleucine derivatives such as 127 have been used as key synthetic intermediates in a number of syntheses of (ϩ)-lactacystin (128) with the result that a number of synthetic strategies have been developed to provide access to this building block. 22, 88 The AA based strategy remains among the shortest and most efficient approaches to this structural unit. 88,89 A related approach has been reported for the enantioselective synthesis of the hexahydroazepine core of (Ϫ)-balanol (129).…”
Section: Reverse Regioselectivitymentioning
confidence: 99%
“…It has been shown that human cancer cells are more sensitive to proteasome inhibition than normal cells, indicating that proteasome inhibitors could be used as novel anticancer drugs. [7] Therefore, inhibition of the 20S core particle in the 26S proteasome by substrate modifications such as alkylations, and ring formations has been demonstrated by a number of organic species such as lactacystin,[8] macrocyclic esters,[9] epoxyketones,[10] and several peptide derivatives,[11] including recently FDA-approved boronates. [12,13] The premise that stoichiometric mixtures of copper ions with organic chelators can form a new class of proteasome inhibitors has been investigated by the Dou group in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…10 (+)-Lactacystin was shown to inhibit the 20 S proteasome and subsequent investigations have shown that it acts as a prodrug for its b-lactone, known as clasto-lactacystin b-lactone or omuralide (22), which is responsible for acylating the proteasome. 11 Structure activity relationships have demonstrated that the only replaceable group in the molecule that retains the biological activity is the C4 methyl group. Accordingly we designed our approach to (+)-22 in order to provide a flexible route amenable to analogue synthesis at this position (Scheme 5).…”
Section: Reduction Of Pyrrolesmentioning
confidence: 99%
“…11 Osmium-catalyzed oxidative cyclization for the diastereoselective synthesis of cis-THFs and pyrrolidines.Scheme 12 Preparation of diol 49 via selective asymmetric dihydroxylation of tetradecatetraene(47).Scheme 13 Double oxidative cyclization of 50 for the synthesis of cis-sylvaticin: (i) NaIO 4 , CH 2 Cl 2 , 89%; (ii) C 11 H 23 PPh 3 + Br À , KHMDS, PhMe, À78 1C-rt, 91%. Downloaded by State University of New York at Albany on 20 October 2012 Published on 19 October 2012 on http://pubs.rsc.org | doi:10.1039/C2CC36040C View Online This journal is c The Royal Society of Chemistry 2012 Chem.…”
mentioning
confidence: 99%